Studying of Influence of Nitrile Rubber Adding on Some Physical, Mechanical and Thermal Properties of Unsaturated Polyester Resin - رامي حنا منصور; هادي عبد الكريم معلا; ياسر يوسف قره فلاح (Latakia University Journal -Engineering Sciences Series, 2022)
This research aims to study the effect of nitrile rubber on the mechanical, physical and thermal properties of the unsaturated polyester resin ( UPR ). To achieve this aim, different percentages of rubber were added up to 15% and their effect on the tensile curves, density and hardness, as well as on each of the heat capacity and thermal conductivity were studied. The experimental results showed a clear decrease in the density, surface hardness and tensile stress, while an improvement in both the relative elongation and heat capacity was observed with the increase in the percentage of added rubber.